Analysis of Drought-Induced Proteomic and Metabolomic Changes in Barley (Hordeum vulgare L.) Leaves and Roots Unravels Some Aspects of Biochemical Mechanisms Involved in Drought Tolerance - Chmielewska, Klaudia; Rodziewicz, Paweł; Swarcewicz, Barbara; Sawikowska, Aneta; Krajewski, Paweł; Marczak, Łukasz; Ciesiołka, Danuta; Kuczyńska, Anetta; Mikołajczak, Krzysztof; Ogrodowicz, Piotr; Krystkowiak, Karolina; Surma, Maria; et al. (Frontiers in Plant Science, 2016)
In this study, proteomic and metabolomic changes in leaves and roots of two barley (Hordeum vulgare L.) genotypes, with contrasting drought tolerance, subjected to water deficit were investigated. Our two-dimensional electrophoresis (2D-PAGE) combined with matrix-assisted laser desorption time of flight mass spectrometry (MALDI-TOF and MALDI-TOF/TOF) analyses revealed 121 drought-responsive proteins in leaves and 182 in roots of both genotypes. Many of the identified drought-responsive proteins were associated with processes that are typically severely affected during water deficit, including photosynthesis and carbon metabolism. However, the highest number of identified leaf and root proteins represented general defense mechanisms. In addition, changes in the accumulation of proteins that represent processes formerly unassociated with drought response, e.g., phenylpropanoid metabolism, were also identified. Our tandem gas chromatography – time of flight mass spectrometry (GC/MS TOF) analyses revealed approximately 100 drought-affected low molecular weight compounds representing various metabolite types with amino acids being the most affected metabolite class. We compared the results from proteomic and metabolomic analyses to search for existing relationship between these two levels of molecular organization. We also uncovered organ specificity of the observed changes and revealed differences in the response to water deficit of drought susceptible and tolerant barley lines. Particularly, our results indicated that several of identified proteins and metabolites whose accumulation levels were increased with drought in the analyzed susceptible barley variety revealed elevated constitutive accumulation levels in the drought-resistant line. This may suggest that constitutive biochemical predisposition represents a better drought tolerance mechanism than inducible responses.